Hak Kekayaan Intelektual sebagai Investasi Pembangunan Kota Baubau - Marsudi; Herie Saksono (Balitbangda Kota Baubau, 2020)
Free trade not only has opened market opportunities for domestic products to international markets, but also opened up opportunities to enter global products into the domestic market. This situation certainly impacts various domestic commodities, including intellectual property (IP) protection. The problem is, have we got to know our IP? This study aims to identify, identify, and map IP in the City of Baubau. The approach used is qualitative with descriptive analysis. Based on the analysis results, it was found that there are two potential intellectual property rights (IPR) in Baubau City. First, communal-based IP, such as traditional dance, folklore, traditional music, traditional rituals, traditional martial arts, traditional medicines, traditional woven fabrics, traditional culinary delights. Second, IP is based on culinary, product design, fashion, crafts, music, performing arts, and appropriate technology. It is also evident that five factors cause the minimum IPR protection in the City of Baubau, namely: (1) limited knowledge of the public and local governments about the importance of IPR protection; (2) limited information from the public and local governments about IPR; (3) community and regional governments still lack appreciation for the findings/creations of the community; (4) budget limitations for the management of IPR protection, both the budget owned by the inventors/creators and the budget provided by the local government to facilitate IP protection in the regions; and (5) limited supporting facilities in the management and management of IPR. It is recommended that the City Government of Baubau carry out improvements and manage potential IPRs in the City of Baubau accompanied by budget support.